Синхронизация в системе сотовой связи стандарта IS-95 - Павкина, Н. А. (ХНУРЭ, 2009)
The given work is devoted to the researching of synchronization in the CDMA systems. Code Division Multiple Access (CDMA) is a method of dividing a radio spectrum to be shared by multiple users through the assignment of unique codes. Base stations in the system distinguish themselves from each other by transmitting different portions of the pseudo-random code. To assure that the time offsets of the code used remain unique, CDMA stations must remain synchronized to a common time reference. The Global Positioning System (GPS) provides this precise common time reference
Keywords: сети связи; стандарт IS-95; синхронизация в системе сотовой связи